Edukasi Kesehatan Ibu Nifas untuk Optimalisasi Layanan Home Care Masa Nifas - Suryatim Pratiwi, Yopi; Yesvi Zulfian; Siskha Maya Herlina; Sri Handayani (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
The postpartum period is a critical six-week phase after childbirth that requires intensive monitoring because mothers undergo physiological and psychological recovery and are at risk of complications such as bleeding, infection, postpartum depression, and lactation disorders. Home-care services provided by midwives play an important role in the early detection of complications, emotional support, and increasing family involvement, and various studies have shown their effectiveness in improving mothers’ knowledge, satisfaction, and health. However, in Indonesia, the utilization of these services remains low due to limited maternal knowledge, financial constraints, and midwives’ busy schedules, further aggravated by the absence of national standards for home-care implementation. A community service initiative in Jempong Baru Subdistrict was therefore carried out to improve postpartum mothers’ knowledge and independence through health education and to strengthen midwives’ capacity in innovative home-care practices. Using lectures supported by audiovisual media and leaflets, the program followed the stages of pre-test, counseling, and post-test, which showed a significant increase in postpartum mothers’ knowledge—from 13% categorized as good to 74% after the intervention. This program not only improved mothers’ skills in self-care but also produced a family-based home-care service model that can be replicated and supports midwives’ roles in community-based midwifery services.